LYUBERTSY STUDY ON MORTALITY RATE IN PATIENTS AFTER CEREBRAL STROKE OR TRANSIENT ISCHEMIC ATTACK (LIS-2). DESIGN AND MEDICAL TREATMENT ESTIMATION - S. A. Boytsov; S. Yu. Martsevich; M. L. Ginzburg; N. P. Kutishenko; L. Yu. Drozdova; A. V. Akimova; A. Yu. Suvorov; M. M. Loukianov; N. A. Dmitrieva; O. V. Lerman; N. Yu. Zhuravskaya; E. V. Daniels; et al. (Столичная издательская компания, 2015)
Aim. Estimation of social, demographic and anamnestic characteristics of patients survived cerebral stroke as well as the medical treatment received by the patients before the reference stroke in the hospital and at discharge within the framework of the stroke register LIS-2 (study of mortality among patients survived stroke in Lyubertsy district). Material and methods. All the patients (637 persons) admitted to the Lyubertsy regional hospital №2 due to stroke from 01.01.2009 to 31.12.2010 were enrolled into the study. Results. 36% were men and 64% were women with mean age of 70.99Ѓ}9.6 years old. 554 (87.0%) patients had history of arterial hypertension and 155 (24.3%) - of atrial fibrillation.147 (23.1%) patients had previous stroke. In-hospital mortality made up 21.8% (mean age of 139 deceased patients was 72.7Ѓ}9.6 years old). 374 (75%) patients were prescribed ACE inhibitors, 421 (85%) - antiplatelet agents, 4 (1%) - warfarin. Statins intake was recommended to 3 (1%) patients. Conclusion. We revealed low frequency of prescription of drugs with proven positive prognostic value in patients after stroke.